2021
DOI: 10.1016/j.ijcard.2021.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interventricular membranous septum length on pacemaker need with different Transcatheter aortic valve implantation systems

Abstract: BackgroundThe need for new permanent pacemaker implantation (PPI) after Transcatheter Aortic Valve Implantation (TAVI) remains a critical issue. Membranous Septum (MS) length is associated with PPI after TAVI. The aim of this study was to identify different MS thresholds for the contemporary THV-platforms. Methods This retrospective, case-control study enrolled all patients who underwent a successful TAVI procedure with contemporary THV-platforms in the Erasmus University Medical Center between January 2016 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…5 A single-center experience extended these insights to other THV platforms and confirmed MS phenotypes at low, intermediate and high risk for PPI based on MS length. 8 The present multi-center study confirmed the association of these different MS phenotypes with new PPI except for the ACURATE THV. The new PPI rate with ACURATE THV remained low across the bandwidth of MS lengths.…”
Section: Discussionsupporting
confidence: 82%
“…5 A single-center experience extended these insights to other THV platforms and confirmed MS phenotypes at low, intermediate and high risk for PPI based on MS length. 8 The present multi-center study confirmed the association of these different MS phenotypes with new PPI except for the ACURATE THV. The new PPI rate with ACURATE THV remained low across the bandwidth of MS lengths.…”
Section: Discussionsupporting
confidence: 82%
“…Implantation depth has previously been identified as an independent predictor for postprocedural conduction disturbances and AVB III in TAVI as well as in suAVR. 4,12,25 Regarding the surgical manipulation in SAVR, suturing techniques have been modified to prevent injuries to the conduction system by sutures of the prosthesis. 29 Still, the current study has its limitations: Although MIS length was cautiously measured and interrater variability was ruled out, overestimations of the MIS in some patients are highly unlikely but still possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to measuring the mere length of the MIS, some authors combined their observations with the surveillance of the implantation depth. [12,25] As the MIS serves as a surrogate for the location of the Bundle of His like discussed earlier, any surgical manipulation during SAVR or mechanical stress due to the nitinol cage of the prosthesis in suAVR may cause an irritation of the vulnerable nerve fibres. Thus, the idea to choose the implantation depth wisely seems to be an axiomatic assumption.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations